FACTORS AFFECTING THE COMMUNITY'S AVAILABILITY FOR THE COVID 19 VACCINATION IN THE RESIDENTS OF MARKET SIPAGIMBAR SUB-DISTRICT, SAIPAR DOLOK HOLE, SELATAN TAPANULI REGENCY IN 2022 - Rini Fitriani Dongoran; Ahmad Syukur Hasibuan (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
One of the latest treatments for Covid-19 is through the administration of vaccines. The vaccination program is one of the government's efforts to control the spread of the Covid-19 virus in Indonesia. Data from the Health Office of North Sumatra Province in January 2022 that people exposed to COVID-19 were 154,688 people. South Tapanuli Regency was exposed to Covid-19 as many as 840 people. Saipar Dolok Hole District was exposed to COVID-19 as many as 7 people. The Pasar Sipagimbar Village has 4 people with COVID-19. The study used a quantitative approach with an observational type with a cross-sectional design. The population is all people aged 18-59 years as many as 1750 people in Pasar Sipagimbar Village, Saipar Dolok Hole District, South Tapanuli Regency. The sample using the slovin formula as many as 95 people. The sampling technique is systematic random sampling. The results of the study showed that from 95 people, the majority of people were in the low category of education, 48 people (50.5%), lack of knowledge in the category of 52 people (54.7%), attitude in the negative category 52 people (54.7%), the availability of information on the location of the vaccine category available. 57 people (60.0%), belief in the poor category 54 people (56.8%), history of non-communicable diseases in the majority category no 64 people (67.4%), community willingness to get COVID-19 vaccination yes category 59 people (62 ,1%). The conclusion is that there is education, knowledge, attitude, availability of location information, confidence with a value of p = 0.000, while vaccines (p = 0.005) and history of non-communicable diseases (p = 0.001) on the community's willingness to vaccinate covid 19 in Pasar Sipagimbar Village, Saipar District Dolok Hole, South Tapanuli Regency. The results of the multivariate variable that most influenced the public's willingness to vaccinate covid 19 was knowledge because it had the largest regression coefficient (B) of 4.290.